Expression Levels of Some Apoptotic and Oxidative Genes in Sheep with Sarcocystosis - Yüksek, Veysel; Orunç Kılınç, Özlem; Dede, Semiha; Çetin, Sedat; Ayan, Adnan (Journal of the Hellenic Veterinary Medical Society, 2022)
Sarcocystosis is a zoonotic protozoon-related disease with a very broad intermediate host spectrum. These protozoon parasites lead to tissue loss in their intermediate hosts. The purpose of this study was to present the mRNA expression levels of some genes belonging to the oxidative stress and apoptosis pathway systems in tissue damage caused by sarcocystosis. In this study, the material consisted of infected tissue taken from sheep esophagus determined to be sarcocystosis-infected and esophageal tissues taken from healthy sheep. The expression levels of the GPX1, SOD1, SOD2, NCF1and Nos2 genes that play a role in the oxidative stress mechanism and the caspase 3, 8, 9 and BCL-2 genes that play a role in the apoptosis mechanism were determined by RT-qPCR. As a result of the study, it was determined that, with increased oxidative stress, the gene expressions related to the relevant enzyme systems also increased, and in relation to this increase, the caspase enzyme genes that are effective in cell death were up-regulated. These results may shed light on similar studies for understanding and preventing damage mechanisms that may form as a result of sarcocystosis. As a result, it is understood that increased oxidative stress parameters and increased apoptosis in sarcocystic tissue in sheep cause tissue loss. We think that understanding the molecular mechanisms of this disease is clinically important in the treatment of parasitic diseases and in the prevention of economic losses that may occur as a result of the disease.